Effect of different combination of music and rhytmic movements on behavioral problems of 8-14 year old boys with mental retardation - Maryam Nazari; Ahmadreza Movahedi; Shila Safavi Homami (University of Tehran, 2015)
The main purpose of the present study was to investigate the effect of different combinations of music and rhythmic movements on behavioral problems of children with mild mental retardation. A total of 40 children with mild mental retardation were randomly divided into 4 variations of practice including: rhythmic movement with major scale music, rhythmic movement with minor scale music, rhythmic movement with no music, and no rhythmic movement-no music (control group). Rutter inventory (Parent version) was used to evaluate behavioral problems. Pretest was taken before the intervention and post-test was taken after 12 weeks of practice (36 sessions). For data analysis, one-way analysis of variance and Tuki follow up tests were used. Results showed that behavioral problems of rhythmic movement with major scale music group were significantly decreased. It was also shown that the rhythmic movement with minor scale music and rhythmic movement with no music showed no significant decrease on behavioral problems of mentally retarded children. No considerable change was found in behavioral problems of the participants of the control group.